A comparative assessment of the financial costs and carbon benefits of REDD+ strategies in Southeast Asia. (15th November 2016) - Graham, Victoria; Laurance, Susan G; Grech, Alana; McGregor, Andrew; Venter, Oscar
Abstract: REDD+ holds potential for mitigating emissions from tropical forest loss by providing financial incentives for carbon stored in forests, but its economic viability is under scrutiny. The primary narrative raised in the literature is that REDD+ will be of limited utility for reducing forest carbon loss in Southeast Asia, while the level of finance committed falls short of profits from alternative land-use activities in the region, including large-scale timber and oil palm operations. Here we assess the financial costs and carbon benefits of various REDD+ strategies deployed in the region. We find the cost of reducing emissions ranges from 9 to 75 per tonne of avoided carbon emissions. The strategies focused on reducing forest degradation and promoting forest regrowth are the most cost-effective ways of reducing emissions and used in over 60% of REDD+ projects. By comparing the financial costs and carbon benefits of a broader range of strategies than previously assessed, we highlight the variation between different strategies and draw attention to opportunities where REDD+ can achieve maximum carbon benefits cost-effectively. These findings have broad policy implications for Southeast Asia. Until carbon finance escalates, emissions reductions can be maximized from reforestation, reduced-impact logging and investing in improved management of protected areas. Targeting cost-efficient opportunities for REDD+ is important to improve the efficiency of national REDD+ policy, which in-turn fosters greater financial and political support for the scheme.